Caracterização de Cercospora coffeicola por filogenia molecular multigênica - Vale, Paula Adrielly Souza (2016)
The brazilian coffee is an agricultural activity that leverages the economy, generating remarkable dividends for the country. Because of its considerable importance, it is pertinent to study any factor affecting coffee production in the country. The fungus Cercospora coffeicola Berk. & Cooke, etiological agent of the brown eye spot, although causes notable losses in crops is little studied and effective management strategies to control the disease are scarce. Aiming to address these issues, the aim of this study was to characterize isolates of Cercospora coffeicola from the main producing regions of Brazil. Another objective of this study was epitify the species, which had so far a confusing taxonomy. The presence of atypical symptoms of the disease in crops was a evidence of occurrence of variability within the population of C. coffeicola. Then a representative sample containing 19 isolated from the states of Minas Gerais, São Paulo, Paraná, Bahia and Espirito Santo was characterized at the molecular level. The phylogenetic approach was a multi-locos approach. This was based on the combination of partial sequences derived from the locos ITS (Internal Transcribed Spacer) along with four parts of genes encoding the proteins actin (ACT), calmodulin (CAL) and TEF-1α (elongation factor). All genes were individually evaluated by the method of Maximum parsimony, and a monophyletic group was formed, with reference isolated from other countries. This allows us to state that the same species can cause two types of symptoms in crops and be classified as just a phylogenetic species. There wasn’t variation between isolates from different locations, which can be considered favorable for breeding programs for resistance to the fungus, since the pathogen control is facilitated via improvement in species with low occurrence of variability. The sequences generated in this study were deposited in GenBank, and alignment and tree in TreeBASE for future reference tool for the understanding of plant-pathogen relationship and consequently the progress of breeding programs.